A real option approach for the valuation of switching output flexibility in residential property investment. Issue 2 (6th August 2018) - Mintah, Kwabena; Higgins, David; Callanan, Judith
Abstract : Purpose: Uncertainties in residential property investment performance require that real estate assets are designed in a flexible manner to respond to impacts of market dynamics. Though estimating the cost of flexibility is straightforward, assessing the economic value of flexibility is not. The purpose of this study is to explore the potential practical application of real option analysis to determine the economic value of a switching output flexibility embedded in a residential property investment in Australia. The study involves the exploration of an optimal strategy for investment in a residential development through real option analysis and valuation of a mixed use investment. Design/methodology/approach: The real option valuation model developed byMcDonald and Siegel (1986 ) is adopted for the evaluation because the switching output flexibility is likened to a perpetual American call option with dividend payout. Findings: Through real option analysis, the economic value of switching output flexibility of the mixed use building was determined to be higher than the initial upfront costs. Moreover, a payoff of about $4million was determined to be the value of the switching output flexibility, therefore justifying upfront investments in flexibility as an uncertainty and risk management tool. Practical implications: This application is an important demonstration of the practical use of options pricing techniques (real options analysis) and delivers further evidence needed to support the adoption of real option valuation in practice. Flexibility can also enhance risks and uncertainty management in residential property investment better than the adjustment of discount rates. Originality/value: There is limited evidence on the use of real options techniques for the valuation of switching output flexibility in practice, and this comes as an original application; both the case study and data are all initial applications of switching flexibility in the Australian property market.